Basel II – Benefits for Developing Countries? - Martina Metzger (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
The major target of the new capital accord which was adopted in 2004 and is implemented not before 2007 is to prevent bad banking by introducing more risk-sensitive capital requirements. This paper analyses the impacts of Basel II on developing countries which have been most strongly affected by bad banking. The paper identifies structural, price and displacement effects of Basel II which will change international lending to developing countries. While lower-rated developing countries' access to international capital markets will be restrained even further, an accumulation of foreign debt by higher-rated developing countries will be encouraged. Moreover, the new capital accord induces structural and displacement effects on credit markets in developing countries themselves. Due to the use of different approaches toward the measurement of risk, domestic banks will loose competitiveness against subsidiaries of internationally operating banks. For the former this will result in an increased vulnerability to shocks and financial crises.
Keywords: E44; F34; G15; G28; 330